Socially responsible knowledge and behaviors: comparing upper- vs. lower-classmen - Kozar, Joy M.; Hiller Connell, Kim Y. (My University, 2011)
Utilizing a sample of undergraduate students and survey research methods, this study examined knowledge on issues of social responsibility within the apparel and textiles industry, comparing the sophistication among upper- versus lower-classmen. The study also investigated the differences between students in their socially responsible apparel purchasing behavior. Findings revealed that approximately half of the sample indicated being knowledgeable about socially responsible clothing businesses. Participants were also generally informed of environmental issues related to apparel production. Overall, upper-classmen were more informed about labor issues and tended to be more engaged in socially responsible apparel purchasing behavior. The findings of this study are useful to educators in creating effective curriculum to encourage greater socially responsible purchasing behavior.
Keywords: College students; Social responsiblity; Apparel industry; Purchasing behavior; Labor standards; Environmental issues